Case report: Ipilimumab and nivolumab in metastatic adrenocortical cancer with high tumor mutational burden - Mispelbaum, Rebekka; Hattenhauer, Tessa; Bauernfeind, Franz-Georg; Lau, Jan-Frederic; Brossart, Peter; Heine, Annkristin (Frontiers in Oncology, 2024)
In the setting of metastatic adrenocortical cancer, there are limited therapy options such as mitotane and platinum-based chemotherapy with only low response rates. Ipilimumab and nivolumab are approved for several solid cancer types. Tumor mutational burden is one established marker to predict treatment success of immunotherapy and has been associated with improved response rates to immune checkpoint inhibitors. We here present the case of a 68-year-old woman with metastatic adrenocortical cancer and high tumor mutational burden treated with ipilimumab and nivolumab in a fourth-line setting. She showed a stable disease for at least 48 weeks, which is significantly longer than the treatment response to mitotane or platinum-based chemotherapy. To the best of our knowledge, this is the first successful use of a long-term two-drug immunotherapy (48 weeks) in a patient with metastatic adrenocortical cancer and high mutational burden. Ipilimumab and nivolumab should be considered as a new therapy option in this patient group.